2006
DOI: 10.1108/00070700610688403
|View full text |Cite
|
Sign up to set email alerts
|

Food safety education initiative to increase consumer use of food thermometers in the United States

Abstract: PurposeThe purpose of this research is to increase consumers' use of food thermometers to test the endpoint temperature of small cuts of meats.Design/methodology/approachThe project integrates research, classroom and non‐formal education.FindingsInstant‐read food thermometers were available in >73 percent of USA supermarkets and most were accurate within 1.1°C. Lethality findings include that ground beef patties should either be cooked in a two‐sided grill or turned frequently during cooking. Focus group parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…We found that consumers are much more likely to use a food thermometer for roasts than for smaller cuts of meat like chicken parts and hamburgers. This result is consistent with other research that has found that consumers are resistant to using food thermometers, especially for small cuts of meat (1, 11,17,22,27). Some of the main barriers include that it is difficult to use most food thermometers on small cuts of meat since the tip of the thermometer must be inserted deep enough into the meat to get an accurate temperature and that, in general, food thermometers are hard to calibrate (13).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We found that consumers are much more likely to use a food thermometer for roasts than for smaller cuts of meat like chicken parts and hamburgers. This result is consistent with other research that has found that consumers are resistant to using food thermometers, especially for small cuts of meat (1, 11,17,22,27). Some of the main barriers include that it is difficult to use most food thermometers on small cuts of meat since the tip of the thermometer must be inserted deep enough into the meat to get an accurate temperature and that, in general, food thermometers are hard to calibrate (13).…”
Section: Discussionsupporting
confidence: 94%
“…Previous research examining consumer food handling habits has found that use of food thermometers is relatively low (1 , 11,17,22,27). However, few studies have used nationally representative data to investigate trends of ther mometer usage over time.…”
mentioning
confidence: 97%
“…All the studies identified through electronic database searching were reported in published journal articles. Partial results from two studies (Takeuchi et al, 2005a;Takeuchi et al, 2005b) were also reported in a section of another somewhat larger paper examining food thermometer usage (McCurdy et al, 2006). For the purposes of this paper the studies were only discussed as a part of the original papers as they contained greater detail.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…temperature for the required time, and checking doneness by measuring the internal temperature using a thermometer McCurdy et al, 2006). Only 22.37% of NoI respondents and 21.69% of YesI respondents answered correctly, while the majority (NoI, 77.63%; YesI, 78.31%) relied on sensory observation.…”
Section: Cooking and Food Consumptionmentioning
confidence: 97%